THE INFLUENCE OF PHYSICAL WORK ENVIRONMENT AND NON-PHYSICAL WORK ENVIRONMENT ON EMPLOYEE WORK SATISFACTION AT THE BKPSDMD AGENCY OF MAKASSAR CITY - Taufiq, Farah Ramadhani; Amin, Andi Mustika; Dipoatmodjo, Tenri Sayu Puspitaningsih; Musa, Chalid Imran; Kurniawan, Agung Widhi (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2023)
Employee job satisfaction is a crucial factor that impacts organizational performance and productivity. A satisfied workforce tends to be more engaged, motivated, and committed to their work, leading to improved overall performance. One of the key determinants of job satisfaction is the work environment, both physical and non-physical. This study aimed to examine the impact of the physical work environment and non-physical work environment on employee job satisfaction at the Makassar City Regional Employment and Human Resources Development Agency. The study utilized primary and secondary data, with a sample size of 57 respondents. A quantitative approach was employed, and the data were analyzed using multiple linear regression analysis. The data were processed using SPSS 21 for statistical analysis to test the three hypotheses. The findings of the study revealed that the physical work environment variable had a significant effect on employee job satisfaction (t-statistic = 2.083, p < 0.05), and the non-physical work environment variable also had a significant effect (t-statistic = 5.682, p < 0.05). Furthermore, when considering both the physical work environment and non-physical work environment variables together, they collectively had a significant effect on employee job satisfaction (F-statistic = 89.813, p < 0.05).